SERAT HARDAMUDHA IN JAVANESE LITERATURE: A STUDY OF STRUCTURE, FUNCTION AND MEANING - Kamidjan, Kamidjan; Weda Kusuma, I Nyoman; Setya Yuwana, Setya Yuawana; Suarka, I Nyoman (e-Journal of Linguistics, 2012)
In this study Serat Hardamudha written by Kyai Secanitis is chosen as the object of the study. It is part of a collection at the Sonobudoyo Museum, Yogyakarta, with No. PB A 244 as its collection number. It contains symbols and signs which attracts the researcher’s attention. Such signs can be interpreted as social, moral, religious, and cultural teachings which are so great that they may be utilized as a learning medium in our lives. The problems in this study are formulated as follows: (1) what is the structure of Serta Hardamudha like; (2) what are its functions for our lives; and (3) what meanings it contains? This study aims at analyzing (1)  the structure of Serat Hardamudha; (2)  its functions for our lives; (3)  its meanings. This study is classified as a qualitative one using qualitative data in the forms of words, sentences or concepts taken from the data sources.  The data were obtained from the primary and secondary sources. The primary data source in this study         is a literary work entitled Serat Hardamudha. The secondary data sources include references related to research. The data were collected using note taking technique completed with data cards and note books. The data were descriptively and interpretatively analyzed using hermeneutic approach. The novelties of the study are that (1) Serat Hardamudha deviated from conventions but contained innovations. From the form point of view, it, especially tembang Dhandhanggula, gatra 3 , deviated from conventions. (2) The massage was symbolically and implicitly presented. (3) Serat Hardamudha presented the life of the Javanese people during colonial era. (4) Serat Hardamudha was written to give enlightenment to the community that ma lima should be eliminated.
Keywords: Serat Hardamudha – a study of structure, function and meaning